Human nutrition - Stephenson, Tammy J.
Human Nutrition: Science for Healthy Living is an interesting, engaging, reliable, and evidence-based introductory textbook with a wide variety of features to promote active learning. A clinical emphasis appeals to all, but is of particular relevance to those studying nutrition, dietetics, or health science professions, including nursing. Real-life and clinical examples, statistics, and evidence from professional sources address current and controversial topics and support the key concepts of the science of nutrition